Fish Oil Finishing Diet Maintains Optimal n-3 Long-Chain Fatty Acid Content in European Whitefish (Coregonus lavaretus) - Suomela, Jukka-Pekka; Tarvainen, Marko; Kallio, Heikki; Airaksinen, Susanna (Springer, 2017)
This study examined the effect of substituting vegetable oil for fish oil in feed, with subsequent re-introduction of fish oil-rich feed (finishing feeding) in late stages of growth, on the fatty acids of cultivated European whitefish (Coregonus lavaretus). Restorative finishing feeding with fish oil-rich feed for 15 and 25 weeks was sufficient to change the total content of nutritionally valuable long-chain n-3 fatty acids, eicosapentaenoic acid (20:5n-3) and docosahexaenoic acid (22:6n-3), to correspond to that of fish fed the fish oil-rich feed throughout their lifespan. Under natural conditions, 15 and 25 weeks correspond to weight gains of 75% and 100% (i.e. doubling), respectively. Also, the fatty acid profile of the fish was restored after finishing periods of 15 and 25 weeks. Limiting the use of fish oil by lowering the overall fat content of the feed (no vegetable oil added) resulted in a decrease in the long-chain n-3 fatty acids. Based on the results, after receiving a vegetable oil-rich diet, restorative fish oil-rich feeding in the last stages of growth in European whitefish is nutritionally justified in order to balance nutritional gain for consumers with sustainable use of finite marine oils. The results encourage commercial efforts to further utilize and optimize finishing feeding practices.
Keywords: siiat; rasvahapot; kalanviljely; ravinto; Coregonus lavaretus; fatty acids; fish culture; food